The Transformation of Islamic Education Communication through the Integration of the Aswaja NU Curriculum and Digital Literacy in the Disruption Era: A Systematic Literature Review - Wahdiansyah Wahdiansyah; Muhammad Reza Bakhtimi; Muhammad Solekhin; Umar Fauzan; Muhammad Abzar Duraesa (Yayasan Zia Salsabila, 2026)
The digital disruption era presents a fundamental challenge for Islamic educational communication, particularly in maintaining moderation values amidst uncontrolled information flows. This study aims to systematically review prior research on the transformation of Islamic educational communication through the integration of Nahdlatul Ulama's Aswaja Curriculum (Aswaja NU) and digital literacy, and to formulate a conceptual model for developing adaptive, moderate, and digitally-oriented Islamic education. This research employs a Systematic Literature Review (SLR) based on PRISMA 2020 Template 1 guidelines (Page et al., 2021), designed for new systematic reviews searching databases and registers only. Searches were conducted across eight academic databases from 2019 to 2026. From an initial 312 identified records, the PRISMA selection process yielded 7 articles meeting the inclusion criteria for comparative analysis. Three major trends were identified: (1) the urgency of reconstructing dialogic pedagogical communication grounded in Aswaja NU values; (2) the importance of Islamically ethical digital literacy competencies as a shield for religious moderation; and (3) the critical need for an integrated curriculum bridging traditional Islamic values with digital ecosystem demands. This article contributes the Integrative Islamic Educational Communication Model (MKPII) as a new conceptual framework linking the Aswaja NU curriculum, digital literacy, and the transformation of Islamic educational communication in the era of disruption.